Salt-tolerant modified cationic starch-based flocculating agent, preparation method thereof and application of flocculating and harvesting microalgae
By modifying starch GTA and DDSA, a salt-resistant modified cationic starch-based flocculant (CDCS) was prepared, which solved the problems of low efficiency and poor salt resistance under high salt conditions, and achieved the following: Effective harvesting of microalgae at high salinity.
Patent Information
- Application Number
- CN202411840903.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Existing flocculants are prone to residues of toxic pollutants in microalgae harvest, have low efficiency and poor salt resistance, making it difficult to effectively harvest microalgae under high salt conditions.
Starch is cationized and hydrophobic modified by GTA and DDSA to prepare a salt-resistant modified cationic starch-based flocculant (CDCS). This flocculant can effectively harvest microalgae at high salinity, and It has a high harvest rate and low dosage.
CDCS maintains a high harvest rate in high salt environment, reaching more than 80%, and has a small amount of flocculant, which has excellent economic value, which solves the low efficiency and poor salt resistance of existing flocculants under high salt conditions. question.
Smart Images

Figure CN119409844A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flocculation materials, and in particular to a salt-tolerant modified cationic starch-based flocculant, a preparation method thereof, and application of flocculation and harvesting microalgae. Background Art
[0002] Microalgae is a single-celled photosynthetic autotrophic microorganism with fast growth rate and strong adaptability. It is widely distributed in various water bodies such as ponds, lakes, rivers and oceans. It is a promising biomass resource that can be used to produce food, feed, fuel and chemical materials. However, one of the bottlenecks in the large-scale production and application of microalgae is the harvesting of microalgae (i.e., concentrating microalgae cells from the culture environment). Due to the small cell size (3-30 μm) and low biomass concentration (0.5-3 g / L), the harvesting of microalgae is difficult and costly. Taking the preparation of biodiesel from microalgae as an example, the cost of the harvesting process accounts for 10%-20% of the total production cost. At present, the most commonly used methods for concentrating microalgae are centrifugation and filtration, but these processes have high energy consumption.
[0003] Coagulation / flocculation is the most promising technology for harvesting microalgae with low cost and low energy consumption. The most commonly used flocculants include inorganic metal salts (such as aluminum salts and iron salts) and organic polymers (such as polyacrylamide). Inorganic metal salts induce flocculation mainly through ionic interactions (charge neutralization or net-catching and sweeping effects); organic polymer flocculants mainly aggregate single cells through charge neutralization and bridging adsorption. However, the use of these two types of flocculants will cause the microalgae biomass to be contaminated with metals or potentially toxic acrylamide residues, and therefore are not suitable for the food or feed industry. In addition, most research reports indicate that induced flocculation is more suitable for freshwater microalgae species. Under high salt conditions, on the one hand, ions in the medium will shield the charged sites of flocculants and microalgae, resulting in a weakening of charge neutralization; on the other hand, the presence of salt may promote the folding and disintegration of polymers, affecting the conformation of flocculants and thus affecting the bridging adsorption effect. Therefore, the preparation of a green, efficient and salt-tolerant flocculant is essential for large-scale harvesting of microalgae biomass under different culture conditions. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a salt-tolerant modified cationic starch-based flocculant and a preparation method thereof and application in flocculating and harvesting microalgae, so as to solve the problems that the existing flocculation materials are prone to cause toxic pollutant residues in the harvesting of microalgae, low efficiency, poor salt resistance and the like.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: A method for preparing a salt-tolerant modified cationic starch-based flocculant comprises the following steps: (1) First, the alkali solution and starch are mixed and stirred, then the modifier solution is added, mixed and reacted, and finally washed and dried to obtain modified starch; (2) Firstly, the alkaline solution is mixed with the modified starch obtained in step (1) and stirred, then epoxypropyltrimethylammonium chloride is added, mixed and reacted, and finally washed and dried to obtain the product.
[0006] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a salt-tolerant modified cationic starch-based flocculant, wherein the starch is subjected to cationic modification and hydrophobic modification by GTA and DDSA to obtain a property having high salt tolerance in the harvesting of microalgae, and a high harvest rate of microalgae can still be maintained under high salinity, and the amount of flocculant used is relatively small. The main mechanisms of CDCS flocculating microalgae in a high-salt environment are: (1) CDCS has strong salt tolerance, can maintain a relatively stretched molecular chain, a relatively large viscosity and a relatively high charge density, and thus exerts a better charge neutralization effect and bridging adsorption effect. (2) CDCS can form larger three-dimensional network flocs in a high-salt environment, and the flocs have stronger shear resistance and re-flocculation ability, and exert a better net capture and sweeping effect during the sedimentation process, thereby achieving an ideal harvest rate.
[0007] Furthermore, in step (1), the alkaline solution is an ethanol solution of NaOH with a concentration of 0.05-0.2 g / mL; the mass volume ratio of starch to alkaline solution is 80-120 g:20-40 mL.
[0008] Furthermore, in step (1), the modifier is dodecenylsuccinic anhydride, the concentration of the modifier solution is 0.3-1 g / mL, and the solvent is ethanol; the volume mass ratio of the modifier solution to the starch is 8-12 mL: 80-120 g.
[0009] Furthermore, in step (1), the temperature of the mixing reaction is 80-100°C, and the time is 50-100 min; and the drying temperature is 40-50°C.
[0010] The beneficial effects of adopting the above-mentioned further technical scheme are as follows: the present invention modifies starch by dodecenylsuccinic anhydride, successfully prepares dodecenylsuccinic anhydride-modified starch, reduces the crystallinity of starch, improves the hydrophobicity of starch, and promotes the molecular association within the molecular chain of the salt-resistant modified cationic starch-based flocculant through the hydrophobic micro-regions formed by the mutual aggregation of hydrophobic groups, so that the flocculant has the characteristics of a hydrophobic associating polymer.
[0011] Furthermore, in step (2), the alkaline solution is an ethanol solution of NaOH with a concentration of 0.01-0.02 g / mL; the volume mass ratio of the alkaline solution, modified starch and glycidyltrimethylammonium chloride is 20-40 mL:80-120 g:10-30 g.
[0012] Furthermore, in step (2), the temperature of the mixed reaction is 60-80°C, and the time is 4-8 h; and the drying temperature is 40-50°C.
[0013] The beneficial effect of adopting the above further technical scheme is: the present invention successfully prepares modified cationic starch by cation modification of starch by epoxypropyltrimethylammonium chloride, and obtains salt resistance through the ionizable positive and negative charge groups contained in the molecule and the reverse polyelectrolyte behavior of the amphoteric polyelectrolyte.
[0014] A salt-tolerant modified cationic starch-based flocculant is prepared by the above preparation method.
[0015] Application of the salt-tolerant cationic starch-based flocculant in microalgae harvesting.
[0016] The present invention has the following beneficial effects: The present invention uses GTA and DDSA to perform cationization modification and hydrophobic modification on starch, and successfully prepares a salt-tolerant modified cationic starch-based flocculant. The flocculant has good salt tolerance in the flocculation harvesting of microalgae, and can still achieve a harvest rate of more than 80% under high salinity, and the amount of flocculant used is small, which has excellent economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The SEM and XRD results of CS, CCS, DCS and CDCS in Experimental Example 1, where (A) is SEM and (B) is XRD; Figure 2 is the CS, CCS, DCS and CDCS in Test Example 1 1 H-NMR and zeta potential results, where (A) is 1 H-NMR, (B) is zeta potential; Figure 3 The harvest rates of CCS and CDCS under different salinities in Experiment 2 vary with dosage, where (A) is 3 ppt, (B) is 10 ppt, (C) is 15 ppt, and (D) is 20 ppt; Figure 4 The photos are the sedimentation effects of CCS and CDCS flocculating microalgae at different salinities in Experiment 2, where (A) is 3 ppt, (B) is 10 ppt, (C) is 15 ppt, and (D) is 20 ppt; Figure 5 are the hydrodynamic diameter, viscosity and zeta potential of CS, CCS, DCS and CDCS at different salinities in Experimental Example 3, where (A) is the hydrodynamic diameter, (B) is the viscosity, and (C) is the zeta potential; Figure 6 The zeta potential changes of the system when CCS and CDCS flocculated microalgae at different salinities in Experiment 3, where (A) is 3 ppt, (B) is 10 ppt, (C) is 15 ppt, and (D) is 20 ppt; Figure 7 The microscopic morphology of flocs formed after CCS and CDCS flocculated microalgae at different salinities in Experiment 3, where (A) is 3 ppt, (B) is 10 ppt, (C) is 15 ppt, and (D) is 20 ppt; Figure 8 The real-time particle size changes of CCS and CDCS flocculated microalgae under different salinities in Experimental Example 3, where (A) is 3 ppt, (B) is 10 ppt, (C) is 15 ppt, and (D) is 20 ppt. DETAILED DESCRIPTION
[0018] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0019] Embodiment 1: A method for preparing a salt-tolerant dodecenylsuccinic anhydride-modified cationic starch-based flocculant comprises the following steps: (1) Preparation of dodecenylsuccinic anhydride modified starch DCS First, 3.0 g of NaOH was dissolved in 30 mL of anhydrous ethanol, and the mixture was evenly sprayed into 100.0 g of corn starch while stirring continuously for alkalization. Then, 6.0 g of dodecenylsuccinic anhydride (DDSA) was dissolved in 10.0 mL of anhydrous ethanol, and the mixture was slowly added dropwise into the alkalized starch while stirring continuously. After mixing evenly, the mixture was reacted at 90°C for 80 min. Finally, the mixture was washed with anhydrous ethanol and dried in vacuum at 45°C to obtain the product.
[0020] (2) Preparation of salt-tolerant dodecenylsuccinic anhydride-modified cationic starch-based flocculant CDCS First, 0.5 g of NaOH was dissolved in 30 mL of anhydrous ethanol, and the mixture was evenly sprayed into 100.0 g of DCS obtained in step (1) and stirred continuously to alkalize the mixture. Then, 20.0 g of glycidyltrimethylammonium chloride was added to the alkalized DCS and mixed evenly, and the mixture was reacted at 70°C for 6 h. Finally, the mixture was washed and purified with anhydrous ethanol until no chloride ions were detected in the washing solution, and vacuum dried at 45°C to obtain the product.
[0021] Embodiment 2: A method for preparing a salt-tolerant dodecenylsuccinic anhydride-modified cationic starch-based flocculant comprises the following steps: (1) Preparation of dodecenylsuccinic anhydride modified starch DCS First, 2.0 g NaOH was dissolved in 30 mL anhydrous ethanol, and the mixture was evenly sprayed into 100.0 g corn starch (CS) while stirring continuously for alkalization. Then, 5.0 g dodecenylsuccinic anhydride (DDSA) was dissolved in 10.0 mL anhydrous ethanol, and the mixture was slowly added dropwise into the alkalized starch while stirring continuously. After mixing evenly, the mixture was reacted at 90°C for 70 min. Finally, the mixture was washed with anhydrous ethanol and dried in vacuum at 45°C to obtain the product.
[0022] (2) Preparation of salt-tolerant dodecenylsuccinic anhydride modified cationic starch-based flocculant First, 0.4 g of NaOH was dissolved in 30 mL of anhydrous ethanol, and the mixture was evenly sprayed into 100.0 g of DCS obtained in step (1) and stirred continuously to alkalize the mixture. Then, 18.0 g of glycidyltrimethylammonium chloride was added to the alkalized DCS and mixed evenly, and the mixture was reacted at 70°C for 5 h. Finally, the mixture was washed and purified with anhydrous ethanol until no chloride ions were detected in the washing solution, and vacuum dried at 45°C to obtain the product.
[0023] Embodiment 3: A method for preparing a salt-tolerant dodecenylsuccinic anhydride-modified cationic starch-based flocculant comprises the following steps: (1) Preparation of dodecenylsuccinic anhydride modified starch DCS First, 4.0 g of NaOH was dissolved in 30 mL of anhydrous ethanol, and the mixture was evenly sprayed into 100.0 g of corn starch (CS) and stirred continuously for alkalization. Then, 7.0 g of dodecenylsuccinic anhydride (DDSA) was dissolved in 10.0 mL of anhydrous ethanol, and the mixture was slowly added dropwise into the alkalized starch and stirred continuously. After mixing evenly, the mixture was reacted at 90 °C for 90 min. Finally, the mixture was washed with anhydrous ethanol and dried in vacuum at 45 °C to obtain the product.
[0024] (2) Preparation of salt-tolerant dodecenylsuccinic anhydride modified cationic starch-based flocculant First, 0.6 g of NaOH was dissolved in 30 mL of anhydrous ethanol, and the mixture was evenly sprayed into 100.0 g of DCS obtained in step (1) and stirred continuously to alkalize the mixture. Then, 22.0 g of glycidyltrimethylammonium chloride was added to the alkalized DCS and mixed evenly, and the mixture was reacted at 70°C for 7 h. Finally, the mixture was washed and purified with anhydrous ethanol until no chloride ions were detected in the washing solution, and vacuum dried at 45°C to obtain the product.
[0025] Comparative Example 1: A method for preparing a modified cationic starch-based flocculant comprises the following steps: First, 0.5 g NaOH was dissolved in 30 mL anhydrous ethanol, sprayed evenly into corn starch (CS) and stirred continuously for alkalization; then 20.0 g glycidyltrimethylammonium chloride was added to the alkalized corn starch and mixed evenly, and reacted at 70 °C for 6 h; finally, it was washed and purified with anhydrous ethanol until no chloride ions were detected in the washing liquid, and then vacuum dried at 45 °C to obtain the modified cationic starch-based flocculant CCS.
[0026] Test Example 1: Characterization of Physicochemical Properties of Flocculants 1. Characterization methods (1) SEM characterization: The DCS and CDCS prepared in Example 1, the CCS prepared in Comparative Example 1, and the raw material CS samples were fixed on plastic films, respectively, and gold was sprayed on the surface. SEM tests were performed using a scanning electron microscope (S-4800, Hitachi, Japan) with a voltage set to 5 kV and a magnification of 1000-2000 times.
[0027] (2) XRD characterization: The XRD spectra of the DCS, CDCS prepared in Example 1, the CCS prepared in Comparative Example 1 and the raw material CS sample were tested in the diffraction angle range of 10°-70° using an X-ray diffractometer (DX-2700, Haoyuan, China), and the crystallinity was calculated using Origin 2021 software.
[0028] (3) 1 H-NMR characterization: DCS, CDCS prepared in Example 1, CCS prepared in Comparative Example 1 and raw material CS samples were dissolved in D2O solvent, transferred to NMR sample tubes, and tested using an NMR spectrometer (DRX-500, Bruker, Germany). 1 H-NMR. The data were solvent corrected using MestReNova 15.0 software, and the chemical shifts were interpreted according to the chemical environment of the hydrogen atoms in the reactants, taking into account the inductive effect, conjugation effect, and local paramagnetic effect.
[0029] (4) Determination of cationic substitution degree (DSC): The total nitrogen content in the DCS and CDCS prepared in Example 1, the CCS prepared in Comparative Example 1 and the raw material CS samples was determined by Kjeldahl nitrogen determination, and DSC calculation was performed according to formula (1).
[0030] Formula (1); Wherein, 162 is the molar mass of anhydroglucose residue (g / mol); ω is the difference in total nitrogen content of the sample before and after cationization modification (%); and 151.6 is the molar mass of GTA (g / mol).
[0031] (5) Determination of degree of anhydride substitution (DSA): Disperse 1.5 g of the DCS or CDCS sample prepared in Example 1 in 20 mL of ethanol, add 15 mL of 2.5 mol / L hydrochloric acid isopropanol solution, and stir for 30 min. Then filter with filter paper and rinse with ethanol until no chloride ions are detected in the filtrate. Finally, completely dissolve the sample on the filter paper in 100 mL of distilled water and titrate with 0.1 mol / L NaOH solution. Use phenolphthalein as an indicator and record the volume of NaOH consumed. Calculate DSA according to formula (2).
[0032] Formula (2); Wherein, 162 is the molar mass of anhydroglucose residue (g / mol); V is the titration consumption volume of NaOH solution (mL); M is the molar concentration of NaOH solution (mol / L); 268 is the molar mass of DDSA (g / mol); W is the dry weight of the sample to be tested (g).
[0033] (6) Contact angle measurement: DCS and CDCS prepared in Example 1, CCS prepared in Comparative Example 1, and the raw material CS sample were pressed into thin sheets on a tablet press. The thin sheets were then placed on a glass slide and the contact angle of the droplet was measured on a contact angle tester (SDC-350, Dongguan Shengding, China).
[0034] (7) Zeta potential characterization: Sample solutions of 0.1 g / L were prepared at pH 4, 7, and 10, respectively, and added to the omega electrode of a zeta potential meter (Litesizer 500, Anton Paar, Austria). The ambient temperature was set at 25 °C and the voltage was set at 20 V.
[0035] 2. Experimental Results Figure 1 Figure (A) shows the microscopic morphology of CS, DCS, CCS and CDCS. CS particles are spherical or elliptical, with a smooth surface and regular arrangement; DCS particles remain elliptical, but the surface is relatively rough; while the particle surfaces of CCS and CDCS are uneven, with sharp corners, and there is a certain degree of adhesion between particles, and the arrangement is disordered. Compared with CS and DCS, the morphology of CCS and CDCS has changed significantly, indicating that the etherification reaction and esterification reaction have changed the microscopic morphology of starch particles to a certain extent. Figure 1As shown in Figure (B), CS and modified CCS, DCS and CDCS all show typical A-type diffraction peaks, with strong diffraction peaks at 15°, 17°, 18° and 23°, respectively, indicating that GTA and DDSA modification will not change the crystal type of starch. After calculation, the crystallinity of CS, CCS, DCS and CDCS is 34.40%, 26.30%, 31.70% and 28.50%, respectively. This shows that etherification and esterification reactions mainly occur in the amorphous region of starch, resulting in a decrease in the crystallinity of starch.
[0036] Figure 2 The middle figure (A) shows 1 The chemical shifts of 3.66 ppm, 3.85 ppm and 3.98 ppm were attributed to the H of CH2- in the starch skeleton, 5.39 ppm to the H of the hydroxyl group in starch, and 4.79 ppm to D2O. The chemical shift of 3.24 ppm was attributed to the N + The three methyl H groups directly connected, the chemical shift of 3.33 ppm is attributed to the H of CH2 connected to the epoxide in GTA, and both shifts appear in CCS and CDCS. The chemical shift of 1.20 ppm is attributed to the methyl H at the end of the long carbon chain of DDSA, and the chemical shift of 1.92 ppm is attributed to the methylene H bound to -CH=CH- in the carbon chain of DDSA, both of which appear in DCS and CDCS. The above results show that CCS, DCS and CDCS were successfully prepared.
[0037] After measurement and calculation, the cationic substitution of CCS and CDCS is 14.1% and 11.8% respectively, while the anhydride substitution of DCS and CDCS is 1.44% and 1.28% respectively. The molar mass of CDCS is greater than that of CCS and DCS of the same mass, so the cationic substitution and anhydride substitution of CDCS are slightly less than that of CCS and DCS of the same mass. The substitution results also show that CCS, DCS and CDCS were successfully prepared.
[0038] The size of the contact angle can reflect the hydrophobicity of a substance, so measuring the contact angle of starch can evaluate whether the hydrophobic modification is successful. The contact angle of DCS obtained after CS was modified by DDSA increased significantly, from 17.78° of CS to 120.67°, indicating that after the esterification reaction between CS and DDSA, the long carbon chain on DDSA was introduced, and the surface properties changed from hydrophilic to hydrophobic. The contact angle of CCS obtained by etherification of CS by GTA was almost unchanged (about 18°), indicating that GTA modification had almost no effect on the hydrophilicity and hydrophobicity of starch. The contact angle of CDCS obtained by etherification of DCS by GTA was 46.208°, which was smaller than DCS, but much larger than CS. The reason may be that the degree of anhydride substitution of CDCS was slightly smaller than that of DCS. In general, compared with CS and CCS, CDCS has stronger hydrophobicity, and its hydrophobicity comes from the 12 C long chain of DDSA. When CDCS is dissolved in water, due to the different polarities of hydrophobic groups and water molecules, the hydrophobic microregions formed by the mutual aggregation of hydrophobic groups can promote the intramolecular association within the CDCS molecular chain. Therefore, CDCS has the characteristics of a hydrophobic associating polymer.
[0039] like Figure 2 As shown in Figure (B), in the pH range of 4 to 10, the zeta potentials of CS, CCS, DCS, and CDCS are -0.7~-11.8 mV, +35.1~23.6 mV, -1.2~-15.6 mV, and +33.2~+18.4 mV, respectively. Since the charge state of the particle surface is affected by the pH of the solution, the zeta potential values of the four all show the rule that acidic conditions are greater than neutral conditions and greater than alkaline conditions. CS and DCS both show negative charge properties, while CCS and CDCS are both positively charged; and the zeta potential values of DCS and CDCS are slightly lower than those of CS and CCS, respectively. The reasons are as follows: (1) Natural starch carries a negative charge, and CCS and CDCS introduce positively charged quaternary ammonium groups after etherification with GTA, thus showing positive charge characteristics; (2) DCS and CDCS introduce negatively charged carboxyl groups after esterification with DDSA, so the negative charge of DCS is stronger than that of CS, while the positive charge of CDCS is weaker than that of CCS. In short, the CDCS molecule contains groups that can be ionized into positive and negative charges, and can obtain salt-resistant properties through the anti-polyelectrolyte behavior of amphoteric polyelectrolytes.
[0040] Test Example 2: Microalgae flocculation performance 1. Experimental Methods The experiment of flocculation and harvesting microalgae was carried out at room temperature using a six-link coagulation tester (ZR4-6, Zhongrun Company, Shenzhen, China). 200 mL of microalgae suspension was added to a 250 mL beaker and stirred at 200 rpm for 1 minute, and then a preset dose of flocculant was added and stirred for 2 minutes to fully mix. Then, the stirring speed was reduced to 50 rpm for 15 minutes to allow the microalgae to flocculate into flocs. Finally, the stirring was stopped, and after settling for 15 minutes, the liquid 2 cm above the liquid surface was aspirated, and the absorbance at a wavelength of 685 nm was measured using an ultraviolet spectrophotometer (UV-7504C, Xinmao, Shanghai, China). The flocculation performance was characterized by the harvest rate (HE), and the calculation formula was: HE (%) = (A1-A2) / A1×100%. Among them, A1 and A2 are the OD values of the microalgae samples before and after flocculation, respectively. 685 value.
[0041] Microalgae samples were purchased from Nanjing Qiheng Fishery Co., Ltd. (Jiangsu, China) and cultured under natural temperature, natural light, and natural ventilation. BG-11 medium was used in an open raceway tank for 10–15 days until the optical density of the algae solution at 685 nm (OD 685 ) reached about 1.50. The basic characteristics of the microalgae samples are as follows: salinity is 3.00±0.02ppt, pH is 7.25±0.02, and the dry weight of microalgae biomass is 0.91±0.04 g / L. Adding NaCl to the above microalgae samples can obtain microalgae samples with different salinities, while ensuring pH, OD 685 and the dry weight of microalgae biomass remained unchanged.
[0042] 2. Experimental Results Figure 3 The effect of CCS and CDCS dosage on the HE of microalgae samples under different salinities is shown. The results show that under the condition of natural salinity of 3 ppt, with the increase of flocculant dosage, the adsorption rate of CCS and CDCS on microalgae first increases and then stabilizes, and both can reach more than 90%. The minimum flocculant dosage when 90% HE is achieved is defined as the optimal dosage. Under the condition of 3 ppt salinity, the optimal dosages of CCS and CDCS are 10 mg / L and 3 mg / L, respectively ( Figure 3(A) Figure). When the salinity of the microalgae sample increases to 100 ppt and 15 ppt, although the dosage of CCS is as high as 100 mg / L, its harvest rate can only reach 57.9% and 44.2%, and the harvest efficiency is low. The CDCS prepared in the present application can achieve a harvest rate of more than 90% at the optimal dosage of only 10 mg / L and 25 mg / L at these two salinities, indicating that the flocculant prepared by the present invention can significantly improve the salt tolerance and flocculation performance, thereby saving the dosage of flocculant. When the salinity of the microalgae is further increased to 20 ppt, the harvest rate is still not ideal when the CCS dosage is as high as 200 mg / L, which is less than 40%, and the increase in dosage does not significantly improve the harvest rate. The main reason is that the positive charge of CCS is shielded in a high-salinity environment and cannot effectively play a charge neutralization role. The CDCS prepared by the present invention still has a good flocculation effect under high salinity, and HE reaches more than 80% at 100 mg / L, and HE continues to increase with the continued increase in dosage.
[0043] Figure 4 The sedimentation effect of CCS and CDCS after flocculation at the best or maximum dosage is shown. When the salinity is 3 ppt, both CCS and CDCS can effectively settle the microalgae cells to the bottom of the beaker, and the supernatant is clear and transparent. When the salinity is 10 ppt, it is observed that after CCS flocculation, the liquid on the upper quarter surface is light green and relatively clear, indicating that the microalgae flocs have been partially settled; when the salinity is 15 ppt and 20 ppt, a large number of microalgae cells are still present in the supernatant after CCS flocculation. The supernatant treated with the CDCS flocculant prepared by the present invention is relatively clear, but the transparency of the supernatant decreases with the increase of salinity. The HE of CDCS decreases at higher salinity. One reason is that high salinity increases the density of the microalgae culture medium, and the microalgae flocs are suspended in the culture medium and are difficult to settle by gravity. Another reason is that the high ionic strength of the high-salinity solution will also shield the cationic charge of CDCS to a certain extent, which is not conducive to charge neutralization. But at the same time, the high polarity in the solution will also enhance the hydrophobic interaction between CDCS molecules, thereby offsetting the negative impact of charge shielding and maintaining the flocculation ability under high salinity.
[0044] Test Example 3: Flocculation Mechanism 1. Experimental Methods (1) Analysis of salt tolerance of flocculants In order to study the salt tolerance of the flocculant, the present invention determines the hydrodynamic diameter, viscosity and zeta potential of the DCS, CDCS prepared in Example 1, the CCS prepared in Comparative Example 1 and the raw material CS samples at flocculation salinities (3 ppt, 10 ppt, 15 ppt and 20 ppt). 0.1 g / L flocculation sample solutions of different salinities were prepared, and their hydrodynamic diameters were measured using a nanoparticle size zeta potential meter (Litesizer500, Anton-Paar, Austria). 2.5 g / L sample solutions of different salinities were prepared, and their viscosities were measured using a rotational viscometer (NDJ-5S, Rirun, China). The speed was set to 60 r / min, and a suitable rotor was selected to ensure that the opening angle was between 15% and 90%, and the data was recorded. 0.1 g / L natural pH sample solutions of different salinities were prepared, and their zeta potential values were measured using a palladium electrode of a zeta potential meter.
[0045] (2) Zeta charge analysis of flocculation system The microalgae samples before and after flocculation were filtered with a 0.45 μm filter membrane, the filtrate was diluted 20 times and added to the Omega electrode, and the zeta potential of the flocculation system was measured using a zeta potential analyzer.
[0046] (3) Analysis of microalgae floc morphology The initial microalgae suspension and the microalgae flocs after flocculation were aspirated and dropped onto a glass slide to prepare a specimen slide, and then the morphology of the microalgae (microalgae cells or microalgae flocs) was observed under a microscope (XSP-63B, Shanghai Optics, China) at a magnification of 10×20 times.
[0047] (4) Real-time particle size analysis of microalgae flocs In order to study the process of floc formation, fragmentation and reflocculation, the present invention monitors the floc particle size in real time. First, the microalgae cells coagulate to form large flocs after adding flocculants, which is the growth stage. When the flocs grow to the maximum particle size and remain stable, they enter the initial stabilization stage. After the initial stabilization stage, the stirring speed is increased to 350 rpm for 5 minutes, so that the flocs are broken under the shear force generated by high-speed stirring, which is the fragmentation stage. Subsequently, the stirring speed is reduced to 50 rpm for 15 minutes to allow the broken flocs to reflocculate, which is the reflocculation stage. When the flocs grow to the maximum particle size again and remain stable, they enter the final stabilization stage. The floc particle size distribution is monitored in real time using a laser particle size analyzer (Betterize 2000, Dandong Better, China), and D is recorded every 30 seconds. 50The strength factor (SF) and recovery factor (RF) of the flocs are calculated as follows: SF (%) = (d2 / d1) × 100%; RF (%) = (d3-d2) / (d1-d2) × 100%. Where d1, d2 and d3 are the average particle sizes (μm) of the flocs in the initial stabilization stage, the crushing stage and the final stabilization stage, respectively.
[0048] 2. Experimental Results (1) Salt tolerance of flocculants The experimental results are as follows Figure 5 As shown. Figure 5 As shown in Figure (A), the hydrodynamic diameters of CCS, DCS and CDCS in low-salinity water solubility are relatively close, and CDCS is slightly larger than CCS and DCS, while all three are smaller than CS. The main reason is that starch is degraded to a certain extent during the etherification reaction and esterification reaction. The hydrodynamic diameters of CS and CCS are greatly affected by salinity, decreasing from 18.83 microns and 8.40 microns at 3 ppt salinity to 0.95 microns and 0.98 microns at 20 ppt salinity, respectively. In comparison, DCS and CDCS are less affected by salinity, decreasing from 8.5 microns and 9.33 microns at 3 ppt salinity to 4.05 microns and 4.60 microns. The main reason is that DCS and CDCS introduce hydrophobic 12 C long chains. In a highly polar high-salt environment, the hydrophobic association within the molecule is enhanced, allowing the molecule to remain in a relatively stretched state.
[0049] like Figure 5 As shown in Figure (B), when the salinity increases from 3 ppt to 20 ppt, the viscosity of CS, CCS, DCS and CDCS all decreases, respectively: 2.1 MPa·s decreases to 1.7 MPa·s, 8.25 MPa·s decreases to 1.6 MPa·s, 2.4 MPa·s decreases to 2.0 MPa·s, and 2.5 MPa·s decreases to 1.8 MPa·s. The viscosity of CCS is extremely sensitive to changes in salinity. Due to the curling of the CCS molecular chain, the cross-linking force between molecules is weakened, showing a decrease in apparent viscosity, which can be confirmed by the change in the hydrodynamic diameter. DCS and CDCS show a relatively constant viscosity and strong salt tolerance due to the enhanced hydrophobic association and the increase in physical cross-linking points between molecules.
[0050] like Figure 5As shown in Figure (C), in general, the high salt environment has a charge shielding effect on the charged particles in the solution (whether positively or negatively charged): the zeta potential of negatively charged CS and DCS decreased from 4.3 mV and 5.4 mV at 3 ppt to 1.6 mV and 2.3 mV at 20 ppt; the zeta potential of positively charged CCS and CDCS decreased from 29.6 mV and 28.1 mV at 3 ppt to 2.3 mV and 12.8 mV at 20 ppt. According to the above experimental results, DCS and CDCS modified by DDSA showed stronger salt tolerance. The main reason is that in a high salt environment, the particle diameter of DCS and CDCS with hydrophobic groups is larger, the molecular chain is more stretched, and more charged points are exposed.
[0051] (2) Changes in zeta potential of flocculation system The variation trend of zeta potential in the supernatant after flocculation with flocculant dosage is basically consistent with that of HE, and both increase with the increase of flocculant dosage ( Figure 6 ). At salinities of 3, 10, 15, and 20 ppt, the zeta potentials of the flocculation system were -17.4, -20.4, -29.7, and -31.5 mV when the CCS dosages were 10, 100, 100, and 200 mg / L, respectively; and the zeta potentials of the flocculation system were -30.2, -30.4, -27.1, and -34.5 mV when the CDCS dosages were 3, 10, 25, and 100 mg / L, respectively.
[0052] At the salinity of 3 ppt, where both can achieve good harvesting effects, the zeta potential of CCS and CDCS at the optimal dose is negative, indicating that in the process of flocculating microalgae cells, in addition to playing a charge neutralization role, they can also play a bridging adsorption role, so that the ground system charge can reach an ideal harvest rate when it does not reach the unstable range (-10 mV~+10 mV). Combined with the harvest rate of microalgae at the corresponding salinity and corresponding dose, it can be found that for CCS, at the flocculation effect of 3 ppt salinity, the zeta potential increases significantly with the increase of dose, indicating that it plays a good charge neutralization role. When the flocculation effect is poor, at 10, 15 and 20 ppt salinities, even if the amount of flocculant added is large, the system zeta potential still does not increase significantly, indicating that CCS is subject to a strong charge shielding effect at this time and it is difficult to play a strong charge neutralization role.
[0053] For the CDCS prepared by the present invention, at the optimal dosage under four salinity gradients, the zeta potential value is significantly lower than the zeta potential value when CCS reaches the optimal dosage, indicating that CDCS has charge neutralization and bridging adsorption mechanism. Possible ways include the hydrophobic force of CDCS and the interaction with algae EOM, which makes CDCS have stronger affinity for algae cells and the formed flocs are more hydrophobic, so as to be better separated from the water phase.
[0054] (3) Microscopic morphology of flocs Figure 7 The optical microscope morphology of microalgae cells and flocs formed under the optimal / maximum dose. After adjusting the salinity of the microalgae sample, the algae cells in the microalgae sample without adding flocculants are regular spherical, and the cells are green due to the rich chlorophyll. The distance between cells is relatively even, and some cells show signs of movement during the observation period, indicating that the microalgae cells can be evenly suspended in the culture medium and have strong life activity. Figure 7 As shown in Figure (A), under natural salinity (3 ppt), microalgae cells aggregated together to form larger flocs after flocculation by CCS and CDCS. The difference is that the flocs formed by CCS have clearer boundaries. The floc formation process is that a few microalgae cells condense together to form a floc core under the action of flocculants, and then the floc core attracts the surrounding algae cells to grow continuously to form large flocs under the action of charge neutralization and bridging adsorption. The flocs formed by CDCS are often connected by loose small flocs to form a larger three-dimensional network floc structure. CDCS can adsorb microalgae fine or small flocs through the net capture and sweeping action, which is more conducive to the sedimentation of flocs. Under higher salinity, CCS can only form smaller flocs, which are difficult to separate from water due to the greater buoyancy during the sedimentation process, showing a poor harvest rate. However, CDCS can still form larger three-dimensional network flocs to promote sedimentation.
[0055] (4) Dynamic particle size of flocs In order to compare the size of flocs formed by the two flocculants at different salinities, as well as the shear resistance and reflocculation ability of the flocs, the particle size of the flocs during slow stirring, fast stirring and slow stirring was monitored in real time. The results are as follows: Figure 8 shown.
[0056] At natural salinity (3 ppt), both 10 mg / L CCS and 3 mg / L CDCS can reach HE greater than 90%. At this dosage, the average particle size of flocs formed by CDCS (389.8 μm) is slightly larger than that of CCS (372.3 μm). Under the action of external high shear force, the flocs formed by CDCS can also maintain a larger size with an average particle size of 249.1 μm, while the particle size of flocs formed by CCS is reduced by more than half (160.3 μm). After slow stirring is restored, the broken flocs are aggregated and restored to larger flocs. The flocs re-flocculated by CDCS reach an average particle size of 249.1 μm, while the flocs formed by CCS can only be restored to 198.2 μm. It was calculated that the SF and RF of flocs formed by CDCS were 63.0% and 64.2%, respectively, which were significantly greater than those formed by CCS (43.1% and 17.9%), indicating that the flocs formed by CDCS have stronger shear resistance and recovery ability, and the flocculation performance is more stable in practical applications.
[0057] As the salinity of microalgae increased, the size of flocs formed by CCS and CDCS decreased. When the salinity increased from 10 ppt to 20 ppt, the size of flocs formed by CCS decreased from about 90 μm to 20 μm; CDCS decreased from about 330 μm to 290 μm. The results of the measurement of the average particle size of the flocs in the initial stabilization stage were basically consistent with the floc morphology observed under the microscope. After crushing and re-flocculation, the average particle size of the flocs formed by CDCS can also reach about 200 μm. At 10 ppt, 15 ppt and 20 ppt, the SF of flocs formed by CDCS were 50.1%, 49.5% and 50.6 respectively; the RF were 57.7%, 49.3% and 31.8% respectively. In addition, after floc crushing, reflocculation and sedimentation, the final HE of CDCS at 3 ppt, 10 ppt, 15 ppt and 20 ppt salinities was determined to be 72.0%, 63.6%, 52.8% and 42.2%, respectively, which were significantly higher than the final HE of CCS (45.9%, 29.6%, 16.4% and 12.4%). This shows that in a high-salt environment, CDCS has strong salt tolerance and salt resistance, and the flocs formed can still maintain a large size, which is convenient for the flocs to settle in a high-density culture medium, thereby achieving a more ideal HE.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a salt-tolerant modified cationic starch-based flocculant, characterized in that: The following steps are involved: (1) First, an alkali solution and starch are mixed and stirred, then a modifier solution is added, mixed and reacted, and finally washed and dried to obtain modified starch; (2) Firstly, the alkaline solution is mixed with the modified starch obtained in step (1) and stirred, then epoxypropyltrimethylammonium chloride is added, mixed and reacted, and finally washed and dried to obtain the product.
2. The method for preparing the salt-tolerant modified cationic starch-based flocculant according to claim 1, characterized in that: In the step (1), the alkaline solution is an ethanol solution of NaOH with a concentration of 0.05-0.2 g / mL; the mass volume ratio of starch to alkaline solution is 80-120 g:20-40 mL.
3. The method for preparing the salt-tolerant modified cationic starch-based flocculant according to claim 1, characterized in that: In the step (1), the modifier is dodecenylsuccinic anhydride, the concentration of the modifier solution is 0.3-1 g / mL, and the solvent is ethanol; the volume mass ratio of the modifier solution to the starch is 8-12 mL:80-120 g.
4. The method for preparing the salt-tolerant modified cationic starch-based flocculant according to claim 1, characterized in that: In the step (1), the temperature of the mixing reaction is 80-100°C and the time is 50-100 min; the drying temperature is 40-50°C.
5. The method for preparing the salt-tolerant modified cationic starch-based flocculant according to claim 1, characterized in that: In the step (2), the alkaline solution is an ethanol solution of NaOH with a concentration of 0.01-0.02 g / mL; the volume mass ratio of the alkaline solution, the modified starch and the epoxypropyltrimethylammonium chloride is 20-40 mL: 80-120 g: 10-30 g.
6. The method for preparing the salt-tolerant modified cationic starch-based flocculant according to claim 1, characterized in that: In the step (2), the temperature of the mixed reaction is 60-80°C and the time is 4-8 hours; the drying temperature is 40-50°C.
7. A salt-tolerant modified cationic starch-based flocculant, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the salt-tolerant cationic starch-based flocculant according to claim 7 in flocculating and harvesting microalgae.
Citation Information
Patent Citations
Amphoteric alkenyl succinic starch ester and preparation method for low-viscosity products thereof
CN104231094A
Method for harvesting micro algae applicable to high-efficiency flocculation under wide-salinity condition
CN108728365A
Hydrophobic modified cationic starch flocculant as well as preparation method and application thereof
CN113185640A
Cationic starch nano-silica sol compound flocculant as well as preparation method and application thereof
CN117923625A
Alkyl- and alkenyl-sulfosuccinate starchhalf-esters, a method for the preparation thereof
US4387221A
Cited By
Application and harvesting method for harvesting wide-salinity microalgae through cationic polymer compounded bentonite flocculation
CN120888409A